Channel Allocation Scheme for Cellular Network Using Fuzzy Logic - Shinde, Vikas (Asian Journal of Engineering and Applied Technology, 2018)
This paper, deals fuzzy call admission control scheme to the requirement of quality of service. Quality of service is very critical issue in mobile communication because of dearth of spectrum resource and mobility of consumer and the main parameter is call dropping probable condition which shows the possibility of the extant relation being refusable during mobility. When the consumer’s call suddenly abolished in the term of the connection is more troubling than being obstructed likely on a new call try. Performance of channel allocation scheme is evaluated, using fuzzy control in terms of call dropping probability and channel utilization